Radiographic and computed tomographic evaluation and gait analysis of Brazilian minipigs with syndactyly - Justolin, Pedro L. T. [UNESP]; Rahal, Sheila C. [UNESP]; Agostinho, Felipe S. [UNESP]; Mamprim, Maria J. [UNESP]; Teixeira, Carlos R. [UNESP]; Doiche, Danuta P. [UNESP]; Babicsak, Vivian R. [UNESP] (American Veterinary Medical Association (AVMA), 2016)
OBJECTIVE To characterize a population of Brazilian minipigs with naturally occurring syndactyly by use of plain radiographs and CT images and to evaluate kinetic and temporospatial variables by use of a pressure-sensing walkway. ANIMALS 10 Brazilian minipigs from 6 to 8 months of age (group 1, 5 healthy pigs [body weight, 10.5 to 18.5 kg]; group 2, 5 pigs with syndactyly [body weight, 7.5 to 18.0 kg]). PROCEDURES Forelimbs and hind limbs of all pigs were assessed by use of radiography and CT. Gait was analyzed by use of a pressure-sensing walkway. RESULTS All limbs of all pigs of group 2 had syndactyly. Two forelimbs had complex-1 syndactyly, and 8 forelimbs had complex-2 syndactyly. Four hind limbs had simple syndactyly, 1 hind limb had complex-1 syndactyly, and 5 hind limbs had complex-2 syndactyly. Kinetic and temporospatial values and symmetry indices did not differ between groups. Plantar and palmar surfaces of healthy pigs had 2 areas of maximum pressure, whereas plantar and palmar surfaces of pigs with syndactyly had only 1 area of maximum pressure. CONCLUSIONS AND CLINICAL RELEVANCE In this population of pigs, the most common type of syndactyly was complex-2, and comparison with the healthy group revealed no alteration in kinetic and temporospatial variables. Therefore, results suggested that syndactyly in young minipigs did not cause locomotor disturbances.